2021
DOI: 10.37992/2021.1201.028
|View full text |Cite
|
Sign up to set email alerts
|

Diversity assessment and selection of candidate plus trees of Ailanthus triphysa (Dennst.) Alston in Kerala

Abstract: Ailanthus triphysa [Dennst.] Alston is one of the most important and extensively used trees for making match splints in India. Despite its multiple uses, the genetic variability of the trees is little explored. The study attempted to determine the genetic diversity and select candidate plus trees from various parts of Kerala. Thirty candidate plus trees were selected based on baseline regression of trunk volume to crown volume combined with scoring for qualitative characters. The tree height, GBH, crown diamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The selection of parents for breeding should also account for the special advantage of each cluster and each genotype within a cluster based on the objectives of hybridization (Chahal and Gosal, 2002). Studies conducted in Pinus gerardiana (Kant et al, 2006), Melai dubia (Binu, 2019) and Ailanthus triphysa (Lalnunpuia et al, 2021) also had shown similar trends. Therefore, genetic diversity should be given due consideration while selecting plus trees.…”
Section: Resultsmentioning
confidence: 73%
“…The selection of parents for breeding should also account for the special advantage of each cluster and each genotype within a cluster based on the objectives of hybridization (Chahal and Gosal, 2002). Studies conducted in Pinus gerardiana (Kant et al, 2006), Melai dubia (Binu, 2019) and Ailanthus triphysa (Lalnunpuia et al, 2021) also had shown similar trends. Therefore, genetic diversity should be given due consideration while selecting plus trees.…”
Section: Resultsmentioning
confidence: 73%